Plasmonic optical trap having very large active volume realized with nano-ring structure - Kang, Zhiwen (2013)
The feasibility of using gold nano-rings as plasmonic nano-optical tweezers is investigated. We found that at a resonant wavelength of λ=785  nm , the nano-ring produces a maximum trapping potential of ∼32k B T on gold nanoparticles. The existence of multiple potential wells results in a very large active volume of ∼10 6   nm 3 for trapping the target particles. The report nano-ring design provides an effective approach for manipulating nano-objects in very low concentration into the high-field region and is well suited for integration with microfluidics for lab-on-a-chip applications.